A conceptual decomposition of MINLP models for the design of water-using systems. (16th March 2007) - Alva-Argaez, Alberto; Kokossis, Antonis C.; Smith, Robin
The work presents a systematic methodology for the design of industrial water systems that combines principles of water-pinch (Wang and Smith, 1994a, 1994b) with mathematical programming techniques that enable the imposition of practical constraints and the generalisation of the conceptual tools into multi-contaminant problems. A superstructure model is formulated as an MINLP and solved via decomposition. Layout constraints and flowrates compatible with existing networks can be enforced. Elements of capital and operating cost, including piping are analysed. The solution strategy is based upon a penalty-based search, coupled with an iterative projection procedure. The approach is tested and illustrated on several examples.